Analisis Keterkaitan Neoliberalisme dalam Pembangunan "Smart" Forest City di Indonesia: Peluang dan Tantangan bagi Pembangunan Ibu Kota Negara - Anantakupa, Azhar Gusti; Zalsabilla, Himma (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2024)
The relocation of Indonesia's capital city from Jakarta to IKN Nusantara has become a hot topic of discussion among local and international communities. Polemics from all fields continue to be material, especially the environmental sector. In explaining the resolution of this polemic, the theory of neoliberalism is one of our analytical frameworks which will become our basis for argumentation. In this article we discuss infrastructure governance, governance, green areas, technology, land rehabilitation, deforestation control, and agro forest re-development. We collected some accurate data from various sources and made the IKN masterplan designed by bappenas the main topic of our article. In the end, the Indonesian people will be able to assess the importance of this issue and have a broad insight into the environmental sector in the IKN Nusantara.